El modelo de atención del centro infantil del buen vivir Mushuk Pakari de la comunidad Santa Teresa, parroquia de Simiatug. Estudio de la metodología aplicada en el componente educativo y el componente de participación familiar comunitaria. - Azogue Manobanda;Genova, Consuelo (2013)
Research is conducted on the methodology of the educational component and the component of family and community involvement, the CIBV "Mushuk Pakari" parish Simiátug, Guaranda Canton province of Bolivar, 2012-2013. The comprehensive development of children /as dependent on physicalenvironmental, social, biological and psychological individual and the community. According stimulation scientific theories of child development should strengthen the skills and abilities of the areas of language, cognitive, motor and social staff through recreational activities.